A REVIEW OF THE DEVELOPMENT OF AN UNDERSTANDING OF ANTIBIOTIC INTERACTIONS, FROM MECHANISMS OF ACTION TO NOVEL RESISTANCE AND THE SEARCH FOR NATURAL ALTERNATIVES - Mustafa Kareem AL-Azzawi; Nabaa Abbas Hasan; Mohammed M. Barrak (Journal of Medical Genetics and Clinical Biology, 2024)
Recent research has also highlighted the importance of interspecies signalling in terms of ecology, immunology, and evolution. Despite being frequently linked to the direct inhibition of microbial growth, signalling molecules can transmit data about complex, coordinated regulatory phenomena such as virulence island expression, periodic biosynthetic activity, stress responses, cell density, motility, and biofilm formation. Genetically encoded quorum sensing signals, at low concentrations, increase the spread of horizontally acquired antibiotic resistance genes, modify host immune response profiles, and control the expression of virulence determinants. Antibiotics suppress infectious diseases, facilitate health interventions such as surgery, and improve the treatment outcomes of human and animal diseases (e.g., by minimising morbidity, mortality, and hospital length of stay). However, the emergence of drug-resistant biofilms continues to undermine many therapeutic modalities. These intricate settings that provide antibiotics include the presence of individually resistant cells, non-linear nutrient transport and blockage effects, and limited yet subpopulation-biased genetic plasticity. For the longest time, the mainstay of contemporary medicine has been the use of antibiotics to treat bacterial infections 5. However, the creation and spread of antibiotic resistance, a serious worldwide health concern brought on by the abuse and misuse of antibiotics, constantly jeopardises their function. 2. The decrease in the number of novel, efficacious antibiotics being introduced to the market exacerbates these problems. Optimising the usage of already available antibiotics by learning more about how they behave in the intricate microbial and host ecosystems connected to bacterial illnesses is one way to address this. This involves, but is not limited to, looking into how combinations of antibiotics affect treatment outcomes and how these interactions alter in certain settings to either help or hinder the evolution of antibiotic resistance.